Method for reducing fluorescence half-peak width of core-shell indium phosphide quantum dot through aluminum doping and product thereof

By introducing aluminum in the nucleation step of indium phosphide quantum dots and adding aluminum isopropoxide to the shell preparation, aluminium-doped core-shell-type indium phosphide quantum dots is solved, and a narrower fluorescence half-maximum width and higher quantum yield are achieved.

CN119662236AActive Publication Date: 2025-03-21WUHAN UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411341000.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-03-21
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The quantum yield of indium phosphide quantum dots is low and the fluorescence half-maximum width is too wide, making it difficult to meet the requirements of display applications.

Method used

In the nucleation step of the indium phosphide core, aluminum-doped indium phosphide core is introduced to form an aluminum-doped indium phosphide core, and aluminum isopropoxide is added to the shell preparation, layer by layer to form a gradient zinc sulfide shell, and finally a zinc sulfide shell is formed by zinc acetate treatment.

Benefits of technology

It effectively reduces the fluorescence half-maximum width of core-shell indium phosphide quantum dots, improves quantum yield, and makes the size of the quantum dots more uniform, suitable for large-scale production and commercialization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119662236A_ABST
    Figure CN119662236A_ABST
Patent Text Reader

Abstract

The invention discloses a method for reducing fluorescence half-peak width of core-shell indium phosphide quantum dots through aluminum doping and a product thereof, and belongs to the technical field of luminescent materials. The aluminum isopropoxide is added in the nucleation step of the core-shell type indium phosphide quantum dots and is used for passivating surface defects of the quantum dots, inhibiting formation of defect states and inhibiting Ostwald ripening in the nucleation process, so that the size distribution of cores is more uniform. The method disclosed by the invention has the advantages of simple process, convenience in synthesis and easiness in large-scale production; the prepared core-shell indium phosphide quantum dot has the characteristics of narrower fluorescence half-peak width, higher quantum yield, environmental friendliness and the like, and is suitable for popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of luminescent materials, and in particular to a method for reducing the fluorescence half-peak width of core-shell indium phosphide quantum dots by aluminum doping and a product thereof. Background Art

[0002] Colloidal quantum dots have excellent optical properties. Their energy levels, absorption and fluorescence wavelengths are adjustable with size. They have a wide excitation spectrum and good fluorescence monochromaticity. Therefore, they are widely used in fluorescent probes, cell imaging, quantum dot light-emitting diodes (LEDs), and quantum dot-sensitized solar cells. Colloidal quantum dots have high fluorescence intensity, and the emission wavelength can be easily adjusted according to size and composition changes. Their excellent light absorption characteristics in a wide spectral range and their long-term photostability make them widely studied luminescent materials, which are expected to be widely used in optoelectronic devices such as LEDs, displays, and lasers. At present, the efficiency and operating stability of quantum dot light emitting diodes (QLEDs) using the most advanced cadmium chalcogenide quantum dots have basically met the requirements of commercial displays. However, regulations on cadmium toxicity have severely restricted the application of these cadmium-based quantum dots in commercial displays. Among various types of semiconductor quantum dots (QD) materials, InP-based QDs constitute one of the most promising materials for display applications because (i) their optical band gap can cover the entire visible wavelength by controlling their size and (ii) InP QDs have no toxicity issues compared to cadmium- and lead-containing QD materials.

[0003] Although great progress and breakthroughs have been made in synthesis, the quantum yield and emission width of InP quantum dots are still not as competitive as those of cadmium-based quantum dots. There are some problems to be solved in InP quantum dots, such as many surface defects, low fluorescence quantum yield, and too wide half-peak width to meet the application requirements of display. The quantum yield of InP quantum dots alone is very low, but it can be significantly improved by epitaxial growth of zinc chalcogenides with wide band gaps. In the inventor's prior applications, for example, the Chinese invention patent with publication number CN115710505A discloses a method for reducing the fluorescence half-maximum width of core-shell indium phosphide quantum dots, by introducing a certain amount of ligand zinc halide in the heating step after the indium phosphide core is purified and before the shell (ZnSeS / ZnS) is coated; the addition of the ligand zinc halide, on the one hand, can alleviate the continuous shedding of ligands on the surface of indium phosphide quantum dots during the heating process; on the other hand, the ligand zinc halide combines with indium and phosphorus that are not completely bound to the surface, inhibiting Ostwald ripening during the heating process, making the particle size distribution more uniform, and the spectrum shows that the fluorescence peak half-maximum width (fullwidth at half maxima, FWHM) is smaller. In the Chinese invention patent with publication number CN117487538A, the inventor provides an aluminum-doped indium phosphide core-shell quantum dot with adjustable emission spectrum and a preparation method thereof. In the process of zinc sulfide shell coating, aluminum isopropoxide is used as an aluminum source to dope the shell layer. The reducing aluminum isopropoxide reacts with tri-n-octylphosphine, a solvent of the sulfur source, under trace water and oxygen conditions. The reaction occurs during the entire shell coating process, so that aluminum is finally uniformly doped in the zinc sulfide shell layer in the form of aluminum phosphate. The introduction of trivalent aluminum can reduce the charge mismatch between the zinc sulfide shell layer and the indium phosphide core, and can also passivate the oxidation defects of the indium phosphide core and improve the stability of the shell layer, thereby obtaining core-shell quantum dots with excellent luminescence performance. For example, the Chinese invention patent with publication number CN118289720A provides a two-step method for synthesizing aluminum-doped indium phosphide quantum dots and its products. The inventor passivates the surface defects of indium phosphide quantum dots to make the particle size distribution more uniform, the spectrum shows a smaller half-width of the fluorescence peak, and the quantum yield is also improved; and uses aluminum isopropoxide to form an oxide film on the outer layer of the quantum dots to inhibit the oxidation of the quantum dot core-shell interface, thereby improving the photothermal stability of the quantum dots and alleviating Ostwald ripening.

[0004] In display applications, there are usually strict requirements for the half-width of quantum dots. Specifically, in order to achieve high color purity and good display effects, it is hoped that the half-width of quantum dots is as narrow as possible. A narrower half-width means that the colors are brighter and purer, and various colors can be presented more accurately, improving the image quality and color expression of the display. This can make the displayed image clearer and more vivid, and reduce the mixing and blurring of colors. Common methods for reducing the half-width of quantum dots include optimizing the synthesis process, post-processing technology, and surface modification. Doping can reduce defects on the surface of the material and improve surface roughness, thereby further improving the half-width. Based on the research results of the inventors, the half-width of indium phosphide quantum dots is currently controlled at about 40 nm, and the lowest level can reach 38 nm in actual preparation. It is particularly difficult to further reduce the fluorescence half-width on this basis. It is expected to improve the absorption and fluorescence properties of indium phosphide quantum dots by metal ion doping or surface coating, and even to improve the performance of indium phosphide quantum dot QLED. Therefore, the study of doping synthesis and optical properties of indium phosphide quantum dots is of great significance.

[0005] In summary, developing a new method of reducing the half-width of fluorescence of core-shell indium phosphide quantum dots by aluminum doping to further reduce the half-width of quantum dots has positive significance for promoting the large-scale production and commercialization of indium phosphide quantum dots. Summary of the invention

[0006] In view of the above-mentioned defects of the prior art, in the first aspect of the present invention, a method for reducing the fluorescence half-peak width of core-shell indium phosphide quantum dots by aluminum doping is provided, which has simple process, convenient synthesis and easy large-scale production, and comprises the following steps: (1) Aluminum isopropoxide, an indium source, and a phosphorus source react in a solution environment in the presence of zinc halide, and aluminum is introduced in the preparation of the core layer to form an aluminum-doped indium phosphide core; (2) in a solution environment, the aluminum-doped indium phosphide core is treated with zinc chloride to passivate it, and then a zinc source, a selenium source and a sulfur source are used as shell raw materials, and the shell raw materials are reacted in batches to coat the aluminum-doped indium phosphide core layer by layer to form a gradient zinc selenide sulfur shell layer; (3) A sulfur source is used to react with a gradient zinc sulfide selenide shell to form a zinc sulfide shell; then, the surface of the zinc sulfide shell is treated with zinc acetate in a solution environment to obtain core-shell indium phosphide quantum dots.

[0007] Preferably, in step (1), the indium source includes at least one of indium chloride, indium bromide, indium iodide, and indium acetate; the phosphorus source includes at least one of tri(trimethylsilyl)phosphine, tri(dimethylamino)phosphine, and tri(diethylamino)phosphine; and the zinc halide includes at least one of zinc chloride, zinc bromide, and zinc iodide.

[0008] Preferably, in step (1), the molar ratio of the indium source to the phosphorus source is 1:3-5; the molar ratio of the indium source to the zinc halide is 1:2-5; and the molar ratio of the indium source to aluminum isopropoxide is 1:1-4.

[0009] Preferably, in step (1), the reaction temperature is 120-220° C., and the reaction time is 1-60 min.

[0010] In the present invention, the recovery and purification methods of aluminum-doped indium phosphide cores are various, and those skilled in the art can select a suitable method according to actual conditions and collect the target product after the reaction is completed. As presented in one or more embodiments of the present invention, a desolventizing agent is added to the crude reaction solution obtained by the reaction to precipitate the product, and then the lower precipitate is collected by centrifugation, so as to simply achieve the above purpose. Among them, based on the physical and chemical properties of the product, ethanol, acetone, methanol, etc. are all suitable desolventizing agents.

[0011] Preferably, in step (2), the passivation treatment temperature is 100-150° C., and the treatment time is 1-2 h.

[0012] Preferably, in step (2), the zinc source includes at least one of zinc stearate and zinc (II) acetate; the selenium source includes at least one of selenium and selenium oxide; and the sulfur source includes at least one of sulfur, 1-dodecanethiol and octanethiol.

[0013] Preferably, in step (2), the molar ratio of zinc chloride to indium source is 1:2-5; based on the ratio of the raw material to the indium source in step (1), the molar ratio of the zinc source to the indium source is 1-5:1; the molar ratio of the sulfur source to the indium source is 0.5-10:1; and the molar ratio of the selenium source to the indium source is 0.5-5:1.

[0014] Preferably, in step (2), the reaction temperature is 240-320°C and the reaction time is 1-3 h.

[0015] Further preferably, the shell raw materials are reacted in a solution environment in 4 batches to coat the passivated indium phosphide core layer by layer; the first batch is reacted at 250°C for 2 h; the second batch is reacted at 260°C for 2 h; the third batch is reacted at 270°C for 2 h; and the fourth batch is reacted at 280°C for 3 h.

[0016] In the previous research of the inventor, it was confirmed that the introduction of aluminum element for doping in the preparation of the shell layer is beneficial to reduce the fluorescence half-peak width of the core-shell indium phosphide quantum dots. After the preparation of the aluminum-doped indium phosphide core is completed, the present invention can also add aluminum isopropoxide in the preparation of the shell layer to further optimize the fluorescence half-peak width of the product.

[0017] Furthermore, when the shell material is reacted in a solution environment in 4 batches, aluminum isopropoxide is added during the reaction to dope each layer of the gradient zinc sulfide selenide shell; the molar ratio of aluminum isopropoxide to the sulfur source in step (2) is 0.2-3:1.

[0018] Preferably, in step (3), the sulfur source includes at least one of sulfur, 1-dodecanethiol and octanethiol.

[0019] Preferably, in step (3), the molar ratio of the sulfur source to the indium source in step (1) is 0.5-10:1; and the molar ratio of zinc acetate to the sulfur source in step (3) is 0.25-1:1.

[0020] Preferably, in the step (3), when a sulfur source is used to carry out a surface reaction of the gradient zinc sulfide selenide shell layer, aluminum isopropoxide is added during the reaction to dope the zinc sulfide shell layer; the molar ratio of aluminum isopropoxide to the sulfur source in the step (3) is 1:2-15.

[0021] Preferably, in step (3), the reaction temperature is 190-220°C, and the reaction time is 0.5-2 h; the treatment temperature is 190-220°C, and the treatment time is 0.5-2 h.

[0022] In the present invention, the solution environment involved in each step is created by a suitable type of solvent. Those skilled in the art know that the solvent plays a role in promoting the dispersion of substances and creating a suitable environment for the reaction, and is chemically inert relative to the substrate or product. Therefore, the type or amount of solvent involved in the above reaction can be determined according to the physicochemical properties of the substrate and actual conditions. As presented in one or more embodiments of the present invention, the indium source is soluble in oleylamine, etc., the phosphorus source is soluble in tri-n-octylphosphine, etc., and zinc halide or zinc acetate is soluble in oleylamine, octadecene, etc. Other suitable solvent types can also achieve the purpose of the present invention.

[0023] In a second aspect of the present invention, there is provided a core-shell indium phosphide quantum dot having a narrow fluorescence half-peak width and containing no heavy metal elements, which is prepared by the method of the first aspect of the present invention.

[0024] Based on the above technical scheme, the design concept and principle of the present invention is to introduce a certain amount of aluminum isopropoxide during the nucleation step of indium phosphide. The addition of aluminum isopropoxide can introduce aluminum elements into the core, making the core more uniform in particle size during the formation process, and accompanied by the narrowing of the size of the core. On the one hand, it may be combined with the surface of the quantum dots in the form of Z-type ligands to passivate the surface defects of the indium phosphide quantum dots, making the particle size distribution more uniform, and the spectrum shows that the half-peak width of the ultraviolet absorption peak is smaller, and the quantum yield after shelling is also improved; on the other hand, aluminum isopropoxide can also effectively inhibit Ostwald ripening during the synthesis process, making the particle size distribution of the indium phosphide core more uniform; secondly, the indium phosphide core can also be activated by aluminum isopropoxide, making the growth of the zinc sulfide selenide shell more favorable. Combined with the characterization results, the size of the final quantum dots is larger than that without aluminum doping, indicating that the shell will be thicker after aluminum is doped in the core and then shelled, which further illustrates that the core is activated after aluminum doping, which is conducive to the growth of the shell. In the inventor's previous research, aluminum isopropoxide was introduced into the outer shell layer, the purpose of which was to passivate the core surface defects and improve the quantum yield of quantum dots. In contrast, the treatment of the present invention is more direct and effective than the treatment in the shell layer. Similarly, the core-shell indium phosphide quantum dots prepared by the present invention have the advantages of being free of heavy metal elements and being environmentally friendly, and are suitable for promotion and application.

[0025] Compared with the prior art, the present invention has the following advantages and beneficial effects: The invention provides a method for reducing the fluorescence half-peak width of core-shell indium phosphide quantum dots by aluminum doping, which has the advantages of simple process, convenient synthesis and easy large-scale production.

[0026] The invention provides a core-shell indium phosphide quantum dot, which has the characteristics of narrow fluorescence half-peak width, and its components do not contain heavy metal elements, is environmentally friendly, and is suitable for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is an ultraviolet absorption spectrum (UV-vis) diagram of the aluminum-doped indium phosphide core of Comparative Example 1; Figure 2 is a transmission electron microscope (TEM) image of the aluminum-doped indium phosphide core of Comparative Example 1; Figure 3 A detailed spectrum of aluminum of the X-ray photoelectron spectroscopy (XPS) of the aluminum-doped indium phosphide core of Comparative Example 1; Figure 4 The ultraviolet absorption spectrum and fluorescence spectrum of the core-shell indium phosphide quantum dots of Example 1 are shown in FIG. Figure 5 This is a transmission electron microscope image of the core-shell indium phosphide quantum dots of Example 1; Figure 6 is the ultraviolet absorption spectrum of the undoped indium phosphide core of Comparative Example 2; Figure 7 is a transmission electron microscope image of the undoped indium phosphide core of comparative example 2; Figure 8 The ultraviolet absorption spectrum and fluorescence spectrum of the undoped core-shell indium phosphide quantum dots of comparative example 3; Fig. 9 This is a transmission electron microscope image of the undoped core-shell indium phosphide quantum dots of comparative example 3. DETAILED DESCRIPTION

[0028] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0029] Example 1 A method for reducing the fluorescence half-peak width of core-shell indium phosphide quantum dots by aluminum doping, the steps are as follows: (1) Take 0.8920 g of indium iodide, 0.5998 g of zinc chloride and 0.153 g of aluminum isopropoxide, dissolve the three in a 50 mL three-necked flask containing 12 mL of oleylamine, first evacuate for 1 h, add 2 mL of tri-n-octylphosphine (TOP) solution containing 0.7 mL of tri(dimethylamino)phosphine under argon, heat to 180 °C and react for 5 min; during this period, the color of the solution changes from colorless to orange and then to brown; after 5 min, immediately cool the solution to room temperature, mix the obtained crude indium phosphide core with excess anhydrous ethanol, centrifuge at high speed (10000 rpm, 5 min) to obtain the precipitate, and obtain aluminum-doped indium phosphide core, then completely dissolve it with n-hexane for later use; (2) Mix 6 mL of oleylamine, 6 mL of octadecene and 0.5998 g of zinc chloride in a 100 mL four-necked flask, evacuate the flask at room temperature, and then heat to 130 °C in an argon atmosphere (to place the entire device in an anhydrous and oxygen-free environment) for 1 h to completely dissolve the zinc chloride. At this time, add the aluminum-doped indium phosphide core solution dissolved in n-hexane to the reaction system and collect the n-hexane vapor through a condensation reflux device to complete the passivation. The zinc source (1.0 g zinc stearate dissolved in 4 mL octadecene) and the selenium source and sulfur source (0.8 mmol selenium powder and 0.9 mmol sulfur powder dissolved in 1.25 mL tri-n-octylphosphine) were quickly injected into the reaction bottle and heated to 200 °C and mixed for 30 min; then, the mixture was heated to 250 °C and reacted for 2 h; the zinc source (1.0 g zinc stearate dissolved in 4 mL octadecene) and the selenium source and sulfur source (0.6 mmol selenium powder and 1.8 mmol sulfur powder dissolved in 1.5 mL tri-n-octylphosphine) were injected for the second time and reacted at 260 °C for 2 h; the zinc source (1.0 g zinc stearate dissolved in 4 mL octadecene) and the selenium source and sulfur source (0.4 mmol selenium powder and 2.7 mmol sulfur powder dissolved in 1.75 mL tri-n-octylphosphine) were injected for the third time and reacted at 270 °C for 2 h; the zinc source (1.0 g zinc stearate dissolved in 4 mL octadecene) and the selenium source and sulfur source (0.4 mmol selenium powder and 2.7 mmol sulfur powder dissolved in 1.75 mL tri-n-octylphosphine) were injected for the fourth time and reacted at 270 °C for 2 h. g of zinc stearate dissolved in 4 mL of octadecene) and selenium source and sulfur source (0.2 mmol of selenium powder and 3.6 mmol of sulfur powder dissolved in 2 mL of tri-n-octylphosphine), reacted at 280 °C for 3 h to form a gradient aluminum-doped zinc selenide shell; (3) The temperature was rapidly cooled to 210 °C, 1.5 mL of octanethiol was added, and the reaction was carried out at 210 °C for 30 min. The temperature was then lowered to 190 °C, and zinc acetate solution (2 mmol of zinc acetate dihydrate dissolved in 2 mL of oleylamine and 10 mL of octadecene) was added. The reaction was carried out at 190 °C for 1 h and then cooled to room temperature to obtain crude quantum dots. The crude quantum dots were mixed with anhydrous ethanol in a volume ratio of 1:7. After purification by centrifugal precipitation, the obtained core-shell indium phosphide quantum dots were redispersed in n-hexane.

[0030] Example 2 A method for reducing the fluorescence half-peak width of core-shell indium phosphide quantum dots by aluminum doping. In this embodiment, aluminum isopropoxide is added during the preparation of the gradient aluminum-doped zinc sulfide selenide shell layer. The steps are as follows: (1) Take 0.8920 g of indium iodide, 0.5998 g of zinc chloride and 0.153 g of aluminum isopropoxide, dissolve the three in a 50 mL three-necked flask containing 12 mL of oleylamine, first evacuate for 1 h, add 2 mL of tri-n-octylphosphine (TOP) solution containing 0.7 mL of tri(dimethylamino)phosphine under argon, heat to 180 °C and react for 5 min; during this period, the color of the solution changes from colorless to orange and then to brown; after 5 min, immediately cool the solution to room temperature, mix the obtained crude indium phosphide core with excess anhydrous ethanol, centrifuge at high speed (10000 rpm, 5 min) to obtain the precipitate, and obtain aluminum-doped indium phosphide core, then completely dissolve it with n-hexane for later use; (2) Mix 6 mL of oleylamine, 6 mL of octadecene and 0.5998 g of zinc chloride in a 100 mL four-necked flask, evacuate the flask at room temperature, and then heat to 130 °C in an argon atmosphere (to place the entire device in an anhydrous and oxygen-free environment) for 1 h to completely dissolve the zinc chloride. At this time, add the aluminum-doped indium phosphide core solution dissolved in n-hexane to the reaction system and collect the n-hexane vapor through a condensation reflux device to complete the passivation. Aluminum isopropoxide solution (0.5 mmol aluminum isopropoxide dissolved in 0.5 mL of oleylamine) together with zinc source (1.0 g zinc stearate dissolved in 4 mL of octadecene) and selenium source and sulfur source (0.8 mmol selenium powder and 0.9 mmol sulfur powder dissolved in 1.25 mL of tri-n-octylphosphine) were quickly injected into the reaction bottle and heated to 200 °C and mixed continuously for 30 min; next, the mixture was heated to 250 °C for reaction for 2 h; aluminum isopropoxide solution (0.5 mmol aluminum isopropoxide dissolved in 0.5 mL of oleylamine) together with zinc source (1.0 g zinc stearate dissolved in 4 mL of octadecene) and selenium source and sulfur source (0.6 mmol selenium powder and 1.8 mmol sulfur powder dissolved in 1.5 mL of tri-n-octylphosphine) were injected for the second time and reacted at 260 °C for 2 h; aluminum isopropoxide solution (0.5 mmol aluminum isopropoxide dissolved in 0.5 mL of oleylamine) together with zinc source 1.0 g zinc stearate dissolved in 4 mL of octadecene) and selenium source, sulfur source (0.4 mmol selenium powder and 2.7 mmol sulfur powder dissolved in 1.75 mL tri-n-octylphosphine), react at 270 ℃ for 2 h; the fourth injection of aluminum isopropoxide solution (0.5 mmol aluminum isopropoxide dissolved in 0.5 mL oleylamine) and zinc source (1.0 g zinc stearate dissolved in 4 mL of octadecene) and selenium source, sulfur source (0.2 mmol selenium powder and 3.6 mmol sulfur powder dissolved in 2 mL tri-n-octylphosphine), 280 ℃ for 3 h to form a gradient aluminum-doped zinc selenide shell; (3) The temperature was rapidly cooled to 210 °C, 1.5 mL of octanethiol was added, and the reaction was carried out at 210 °C for 30 min. The temperature was then lowered to 190 °C, and zinc acetate solution (2 mmol of zinc acetate dihydrate dissolved in 2 mL of oleylamine and 10 mL of octadecene) was added. The reaction was carried out at 190 °C for 1 h and then cooled to room temperature to obtain crude quantum dots. The crude quantum dots were mixed with anhydrous ethanol in a volume ratio of 1:7. After purification by centrifugal precipitation, the obtained core-shell indium phosphide quantum dots were redispersed in n-hexane.

[0031] Example 3 A method for reducing the fluorescence half-peak width of core-shell indium phosphide quantum dots by aluminum doping. In this embodiment, aluminum isopropoxide is added during the preparation of the zinc sulfide shell layer. The steps are as follows: (1) Take 0.8920 g of indium iodide, 0.5998 g of zinc chloride and 0.153 g of aluminum isopropoxide, dissolve the three in a 50 mL three-necked flask containing 12 mL of oleylamine, first evacuate for 1 h, add 2 mL of tri-n-octylphosphine (TOP) solution containing 0.7 mL of tri(dimethylamino)phosphine under argon, heat to 180 °C and react for 5 min; during this period, the color of the solution changes from colorless to orange and then to brown; after 5 min, immediately cool the solution to room temperature, mix the obtained crude indium phosphide core with excess anhydrous ethanol, centrifuge at high speed (10000 rpm, 5 min) to obtain the precipitate, and obtain aluminum-doped indium phosphide core, then completely dissolve it with n-hexane for later use; (2) Mix 6 mL of oleylamine, 6 mL of octadecene and 0.5998 g of zinc chloride in a 100 mL four-necked flask, evacuate the flask at room temperature, and then heat to 130 °C in an argon atmosphere (to place the entire device in an anhydrous and oxygen-free environment) for 1 h to completely dissolve the zinc chloride. At this time, add the aluminum-doped indium phosphide core solution dissolved in n-hexane to the reaction system and collect the n-hexane vapor through a condensation reflux device to complete the passivation. The zinc source (1.0 g zinc stearate dissolved in 4 mL octadecene) and the selenium source and sulfur source (0.8 mmol selenium powder and 0.9 mmol sulfur powder dissolved in 1.25 mL tri-n-octylphosphine) were quickly injected into the reaction bottle and heated to 200 °C and mixed for 30 min; then, the mixture was heated to 250 °C and reacted for 2 h; the zinc source (1.0 g zinc stearate dissolved in 4 mL octadecene) and the selenium source and sulfur source (0.6 mmol selenium powder and 1.8 mmol sulfur powder dissolved in 1.5 mL tri-n-octylphosphine) were injected for the second time and reacted at 260 °C for 2 h; the zinc source (1.0 g zinc stearate dissolved in 4 mL octadecene) and the selenium source and sulfur source (0.4 mmol selenium powder and 2.7 mmol sulfur powder dissolved in 1.75 mL tri-n-octylphosphine) were injected for the third time and reacted at 270 °C for 2 h; the zinc source (1.0 g zinc stearate dissolved in 4 mL octadecene) and the selenium source and sulfur source (0.4 mmol selenium powder and 2.7 mmol sulfur powder dissolved in 1.75 mL tri-n-octylphosphine) were injected for the fourth time and reacted at 270 °C for 2 h. g of zinc stearate dissolved in 4 mL of octadecene) and selenium source and sulfur source (0.2 mmol of selenium powder and 3.6 mmol of sulfur powder dissolved in 2 mL of tri-n-octylphosphine), reacted at 280 °C for 3 h to form a gradient aluminum-doped zinc selenide shell; (3) The temperature was rapidly cooled to 210 °C, and a solution of 0.75 mmol of aluminum isopropoxide dissolved in 1.5 mL of octanethiol was added. The mixture was reacted at 210 °C for 30 min. The temperature was then lowered to 190 °C, and a zinc acetate solution (2 mmol of zinc acetate dihydrate dissolved in 2 mL of oleylamine and 10 mL of octadecene) was added. The mixture was reacted at 190 °C for 1 h and then cooled to room temperature to obtain crude quantum dots. The crude quantum dots were mixed with anhydrous ethanol in a volume ratio of 1:7. After purification by centrifugal precipitation, the obtained core-shell indium phosphide quantum dots were redispersed in n-hexane.

[0032] Example 4 A method for reducing the fluorescence half-peak width of core-shell indium phosphide quantum dots by aluminum doping. In this embodiment, aluminum isopropoxide is added during the preparation of the gradient aluminum-doped zinc sulfide selenide shell layer and the zinc sulfide shell layer. The steps are as follows: (1) Take 0.8920 g of indium iodide, 0.5998 g of zinc chloride and 0.153 g of aluminum isopropoxide, dissolve the three in a 50 mL three-necked flask containing 12 mL of oleylamine, first evacuate for 1 h, add 2 mL of tri-n-octylphosphine (TOP) solution containing 0.7 mL of tri(dimethylamino)phosphine under argon, heat to 180 °C and react for 5 min; during this period, the color of the solution changes from colorless to orange and then to brown; after 5 min, immediately cool the solution to room temperature, mix the obtained crude indium phosphide core with excess anhydrous ethanol, centrifuge at high speed (10000 rpm, 5 min) to obtain the precipitate, and obtain aluminum-doped indium phosphide core, then completely dissolve it with n-hexane for later use; (2) Mix 6 mL of oleylamine, 6 mL of octadecene and 0.5998 g of zinc chloride in a 100 mL four-necked flask, evacuate the flask at room temperature, and then heat to 130 °C in an argon atmosphere (to place the entire device in an anhydrous and oxygen-free environment) for 1 h to completely dissolve the zinc chloride. At this time, add the aluminum-doped indium phosphide core solution dissolved in n-hexane to the reaction system and collect the n-hexane vapor through a condensation reflux device to complete the passivation. Aluminum isopropoxide solution (0.5 mmol aluminum isopropoxide dissolved in 0.5 mL of oleylamine) together with zinc source (1.0 g zinc stearate dissolved in 4 mL of octadecene) and selenium source and sulfur source (0.8 mmol selenium powder and 0.9 mmol sulfur powder dissolved in 1.25 mL of tri-n-octylphosphine) were quickly injected into the reaction bottle and heated to 200 °C and mixed continuously for 30 min; next, the mixture was heated to 250 °C for reaction for 2 h; aluminum isopropoxide solution (0.5 mmol aluminum isopropoxide dissolved in 0.5 mL of oleylamine) together with zinc source (1.0 g zinc stearate dissolved in 4 mL of octadecene) and selenium source and sulfur source (0.6 mmol selenium powder and 1.8 mmol sulfur powder dissolved in 1.5 mL of tri-n-octylphosphine) were injected for the second time and reacted at 260 °C for 2 h; aluminum isopropoxide solution (0.5 mmol aluminum isopropoxide dissolved in 0.5 mL of oleylamine) together with zinc source 1.0 g of zinc stearate dissolved in 4 mL of octadecene) and selenium source and sulfur source (0.4 mmol selenium powder and 2.7 mmol sulfur powder dissolved in 1.75 mL of tri-n-octylphosphine), reacted at 270 ° C for 2 h; the fourth injection of aluminum isopropoxide solution (0.5 mmol aluminum isopropoxide dissolved in 0.5 mL of oleylamine) and zinc source (1.0 g of zinc stearate dissolved in 4 mL of octadecene) and selenium source and sulfur source (0.2 mmol selenium powder and 3.6 mmol sulfur powder dissolved in 2 mL of tri-n-octylphosphine), reacted at 280 ° C for 3 h to form a gradient aluminum-doped zinc selenide shell; (3) The temperature was rapidly cooled to 210 °C, and a solution of 0.75 mmol of aluminum isopropoxide dissolved in 1.5 mL of octanethiol was added. The mixture was reacted at 210 °C for 30 min. The temperature was then lowered to 190 °C, and a zinc acetate solution (2 mmol of zinc acetate dihydrate dissolved in 2 mL of oleylamine and 10 mL of octadecene) was added. The mixture was reacted at 190 °C for 1 h and then cooled to room temperature to obtain crude quantum dots. The crude quantum dots were mixed with anhydrous ethanol in a volume ratio of 1:7. After purification by centrifugal precipitation, the obtained core-shell indium phosphide quantum dots were redispersed in n-hexane.

[0033] Comparative Example 1 The aluminum-doped indium phosphide core of this comparative example is prepared in the following manner: Take 0.8920 g of indium iodide, 0.5998 g of zinc chloride and 0.153 g of aluminum isopropoxide, dissolve the three in a 50 mL three-necked flask containing 12 mL of oleylamine, first evacuate for 1 h, add 2 mL of tri-n-octylphosphine solution containing 0.7 mL of tri(dimethylamino)phosphine under argon, raise the temperature to 180 °C and react for 5 min; during this period, the color of the solution changes from colorless to orange and then to brown; after 5 min, immediately cool the solution to room temperature, mix the obtained crude indium phosphide core with excess anhydrous ethanol, centrifuge at high speed (10000 rpm, 5 min) to obtain the precipitate, and obtain aluminum-doped indium phosphide core, which is then completely dissolved in n-hexane.

[0034] Comparative Example 2 The undoped indium phosphide core of this comparative example is prepared in the following manner: Take 0.8920 g of indium iodide and 0.5998 g of zinc chloride, dissolve them in a 50 mL three-necked flask containing 12 mL of oleylamine, first evacuate for 1 h, add 2 mL of tri-n-octylphosphine solution containing 0.7 mL of tri(dimethylamino)phosphine under argon, raise the temperature to 180 °C and react for 5 min; during this period, the color of the solution changes from colorless to orange and then to brown; after 5 min, immediately cool the solution to room temperature, mix the obtained indium phosphide core with excess anhydrous ethanol, centrifuge at high speed (10000 rpm, 5 min) to obtain the precipitate, and then completely dissolve the indium phosphide core with n-hexane.

[0035] Comparative Example 3 The undoped core-shell indium phosphide quantum dots of this comparative example are prepared in the following manner: (1) Take 0.8920 g of indium iodide and 0.5998 g of zinc chloride, dissolve them in a 50 mL three-necked flask containing 12 mL of oleylamine, first evacuate for 1 h, add 2 mL of tri-n-octylphosphine solution containing 0.7 mL of tri(dimethylamino)phosphine under argon, raise the temperature to 180 °C and react for 1 min; during this period, the color of the solution changes from colorless to orange and then to brown; after 1 min, immediately cool the solution to room temperature, mix the obtained indium phosphide core with excess anhydrous ethanol, centrifuge at high speed (10000 rpm, 5 min) to obtain the precipitate, and then use n-hexane to completely dissolve the indium phosphide core; (2) Mix 6 mL of oleylamine, 6 mL of octadecene and 0.5998 g of zinc chloride in a 100 mL four-necked flask, first evacuate the flask at room temperature, and then heat to 130 °C in an argon atmosphere (to place the entire device in an anhydrous and oxygen-free environment) for 1 h to completely dissolve the zinc chloride. At this time, add the indium phosphide core solution dissolved in n-hexane to the reaction system and collect the n-hexane vapor through a condensation reflux device to complete the passivation; The zinc source (1.0 g zinc stearate dissolved in 4 mL octadecene) and the selenium source and sulfur source (0.8 mmol selenium powder and 0.9 mmol sulfur powder dissolved in 1.25 mL tri-n-octylphosphine) were quickly injected into the reaction bottle and heated to 200 °C and mixed for 30 min; then, the mixture was heated to 250 °C for 2 h; the zinc source (1.0 g zinc stearate dissolved in 4 mL octadecene) and the selenium source and sulfur source (0.6 mmol selenium powder and 1.8 mmol sulfur powder dissolved in 1.5 mL tri-n-octylphosphine) were injected for the second time and reacted at 260 °C for 2 h; the zinc source (1.0 g zinc stearate dissolved in 4 mL octadecene) and the selenium source and sulfur source (0.4 mmol selenium powder and 2.7 mmol sulfur powder dissolved in 1.75 mL tri-n-octylphosphine) were injected for the third time and reacted at 270 °C for 2 h; the zinc source (1.0 g zinc stearate dissolved in 4 mL octadecene) and the selenium source and sulfur source (0.4 mmol selenium powder and 2.7 mmol sulfur powder dissolved in 1.75 mL tri-n-octylphosphine) were injected for the fourth time. g of zinc stearate dissolved in 4 mL of octadecene) and selenium source and sulfur source (0.2 mmol of selenium powder and 3.6 mmol of sulfur powder dissolved in 2 mL of tri-n-octylphosphine), reacted at 280℃ for 3 h to form a gradient zinc selenide shell; (3) The temperature was rapidly cooled to 210 °C, 1.5 mL of octanethiol was added, and the reaction was carried out at 210 °C for 30 min. The temperature was then lowered to 190 °C, and zinc acetate solution (2 mmol of zinc acetate dihydrate dissolved in 2 mL of oleylamine and 10 mL of octadecene) was added. The reaction was carried out at 190 °C for 1 h and then cooled to room temperature to obtain undoped crude quantum dots. The crude quantum dots were mixed with anhydrous ethanol in a volume ratio of 1:7, and after purification by centrifugal precipitation, the obtained undoped core-shell indium phosphide quantum dots were redispersed in n-hexane.

[0036] Test Example 1 Examples 1-4 are used as typical examples of the present invention, and the quantum dots prepared in these examples and in comparative examples 1-3 are characterized. The properties of the above-mentioned various quantum dots are tested using ultraviolet absorption and fluorescence spectra, transmission electron microscopy and X-ray photoelectron spectroscopy. The corresponding results are shown in FIG. Figure 1-9 As shown in the transmission electron microscope images, it can be seen that the indium phosphide cores prepared in Comparative Example 1 have better size uniformity than the undoped quantum dots prepared in Comparative Example 2.

[0037] The ultraviolet absorption peak, fluorescence emission peak, half-peak width and quantum yield of the quantum dots prepared in the above examples and comparative examples were statistically analyzed and calculated, wherein the half-peak width was measured using a CaryEclipse fluorescence spectrophotometer (Agilent Technologies), and the concentration of the test solution was 0.5 mg / mL. The characterization results of the optical properties of the quantum dots are shown in Table 1. Table 1: Quantum dot optical properties characterization results

[0038] In the table, “ / ” means there is no data available for testing.

[0039] As can be seen from the table above, the quantum dots after the core is doped with aluminum in Comparative Example 1 of the present invention can be successfully doped with aluminum as shown in the XPS spectrum in Figure 3. Figure 1 , Figure 6 From the UV absorption spectrum of the nucleus, it can be seen that the peak-to-valley ratio of the nucleus increases, indicating that the addition of aluminum during nucleation effectively inhibits Ostwald ripening; Figure 2 , Figure 7 It can be seen from the TEM figure that the addition of aluminum during nucleation can make the particle size distribution of the obtained indium phosphide core more uniform. The fluorescence emission peak position of the indium phosphide quantum dots obtained after doping with aluminum in Examples 1-4 of the present invention remains near 530 nm, which is green light emission. Compared with Comparative Example 3, after adding a certain proportion of aluminum isopropoxide to Examples 1-4, the half-peak width of the quantum dots is obviously narrowed, from 44 nm to 35-37nm. This shows that the method provided by the present invention can significantly improve the size uniformity of core-shell indium phosphide quantum dots, which can be more intuitively felt from the corresponding TEM. At the same time, compared with the comparative example, after adding a certain proportion of aluminum isopropoxide to Examples 1-4, the quantum yield has been significantly improved, from 67% to 76%-86%. This shows that the method provided by the present invention can alleviate Ostwald ripening in the synthesis process, reduce the half-peak width of quantum dots, and improve the luminous efficiency and performance of quantum dots.

[0040] Combined with the above test results, it can be seen that the main role of adding aluminum to the core is to make the particle size of the core more uniform during the formation process. It can be seen from the ultraviolet absorption diagram that the corresponding peak type is narrower, indicating that the particle size of the core is more uniform. The introduction of the outer shell layer is mainly to passivate the surface defects of the core and improve the quantum yield of the quantum dots. Therefore, it is more direct and effective to treat the core than to treat the shell. The half-peak width can be reduced to a lower level, reaching a minimum of 35 nm. When aluminum is added to the core, it can be observed that the size of the core is narrowed, but the final size of the quantum dot is larger than that without aluminum doping, indicating that after aluminum is doped in the core and then the shell is formed, the shell will be thicker, which further shows that aluminum doping in the core is conducive to the growth of the shell, and the core is activated in this process.

[0041] It is a huge technical challenge to further reduce the fluorescence half-width based on the previous research of the inventor. The difficulty of this further optimization is reflected in the defects of the system itself. The fundamental problem is that when synthesizing indium phosphide quantum dots, the choice of phosphorus source is limited, and the activity of the phosphorus source is very strong. When the phosphorus source is injected into the indium source at high temperature, the phosphorus source will instantly combine with indium, and the concentration of the formed monomer will quickly reach the critical concentration. Therefore, nucleation will be rapid at the moment of injection, and because the phosphorus source is too active, there is not enough phosphorus monomer for subsequent growth. The nucleated particles will be ripened at high temperature, and ripening will cause the particle size distribution to be uneven, so the peak width will become wider. In the present invention, aluminum is introduced in the preparation of the core to suppress the Ostwald ripening in the above-mentioned nucleation process, thereby solving the process defects of the prior art.

[0042] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A method for reducing the fluorescence half-peak width of core-shell indium phosphide quantum dots by aluminum doping, characterized in that: The steps include: (1) Aluminum isopropoxide, an indium source, and a phosphorus source react in a solution environment in the presence of zinc halide, and aluminum is introduced in the preparation of the core layer to form an aluminum-doped indium phosphide core; (2) in a solution environment, the aluminum-doped indium phosphide core is treated with zinc chloride to passivate it, and then a zinc source, a selenium source and a sulfur source are used as shell raw materials, and the shell raw materials are reacted in batches to coat the aluminum-doped indium phosphide core layer by layer to form a gradient zinc selenide sulfur shell layer; (3) A sulfur source is used to react with a gradient zinc sulfide selenide shell to form a zinc sulfide shell; then, the surface of the zinc sulfide shell is treated with zinc acetate in a solution environment to obtain core-shell indium phosphide quantum dots.

2. The method for reducing the fluorescence half-width of core-shell indium phosphide quantum dots by aluminum doping according to claim 1, characterized in that: In the step (1), the indium source includes at least one of indium chloride, indium bromide, indium iodide, and indium acetate; the phosphorus source includes at least one of tri(trimethylsilyl)phosphine, tri(dimethylamino)phosphine, and tri(diethylamino)phosphine; the zinc halide includes at least one of zinc chloride, zinc bromide, and zinc iodide; the molar ratio of the indium source to the phosphorus source is 1:3-5; the molar ratio of the indium source to the zinc halide is 1:2-5; and the molar ratio of the indium source to aluminum isopropoxide is 1:1-4.

3. The method for reducing the fluorescence half-peak width of core-shell indium phosphide quantum dots by aluminum doping according to claim 1, characterized in that: In the step (1), the reaction temperature is 120-220°C and the reaction time is 1-60 min.

4. The method for reducing the fluorescence half-width of core-shell indium phosphide quantum dots by aluminum doping according to claim 1, characterized in that: In the step (2), the zinc source includes at least one of zinc stearate and zinc (II) acetate; the selenium source includes at least one of selenium and selenium oxide; the sulfur source includes at least one of sulfur, 1-dodecanethiol, and octanethiol; the molar ratio of zinc chloride to indium source is 1:2-5; based on the ratio of the raw material to the indium source in step (1), the molar ratio of the zinc source to the indium source is 1-5:1; the molar ratio of the sulfur source to the indium source is 0.5-10:1; and the molar ratio of the selenium source to the indium source is 0.5-5:

1.

5. The method for reducing the fluorescence half-peak width of core-shell indium phosphide quantum dots by aluminum doping according to claim 1, characterized in that: In the step (2), the reaction temperature is 240-320°C, and the reaction time is 1-3 h; the passivation treatment temperature is 100-150°C, and the treatment time is 1-2 h.

6. The method for reducing the fluorescence half-peak width of core-shell indium phosphide quantum dots by aluminum doping according to claim 5, characterized in that: The shell raw materials were reacted in a solution environment in 4 batches to coat the passivated indium phosphide core layer by layer; the first batch was reacted at 250 °C for 2 h; the second batch was reacted at 260 °C for 2 h; the third batch was reacted at 270 °C for 2 h; and the fourth batch was reacted at 280 °C for 3 h.

7. The method for reducing the fluorescence half-peak width of core-shell indium phosphide quantum dots by aluminum doping according to claim 6, characterized in that: When the shell material is reacted in a solution environment in 4 batches, aluminum isopropoxide is added during the reaction to dope each layer of the gradient zinc sulfide selenide shell layer; the molar ratio of aluminum isopropoxide to the sulfur source in step (2) is 0.2-3:

1.

8. The method for reducing the fluorescence half-width of core-shell indium phosphide quantum dots by aluminum doping according to claim 1, characterized in that: In the step (3), the sulfur source includes at least one of sulfur, 1-dodecanethiol, and octanethiol; the molar ratio of the sulfur source to the indium source in step (1) is 0.5-10:1; the molar ratio of zinc acetate to the sulfur source in step (3) is 0.25-1:1; the reaction temperature is 190-220°C, and the reaction time is 0.5-2 h; the treatment temperature is 190-220°C, and the treatment time is 0.5-2 h.

9. The method for reducing the fluorescence half-peak width of core-shell indium phosphide quantum dots by aluminum doping according to claim 1, characterized in that: In the step (3), when a sulfur source is used to carry out a surface reaction of the gradient zinc sulfide selenide shell layer, aluminum isopropoxide is added during the reaction to dope the zinc sulfide shell layer; the molar ratio of aluminum isopropoxide to the sulfur source in step (3) is 1:2-15.

10. A core-shell indium phosphide quantum dot, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for reducing fluorescence half-peak width of core-shell indium phosphide quantum dots

    CN115710505A

  • Aluminum-doped semiconductor quantum rod and preparation method and application thereof

    CN108329913A

  • Preparation method for InP-based alloy quantum dot, quantum dot, apparatus and composition

    CN108893119A

  • Preparation method of Ga-doped water-soluble InP quantum dot

    CN113512416A

  • Environment-friendly copper gallium aluminum sulfur zinc sulfide core-shell quantum dot and preparation method and application thereof

    CN114891496A